TRANSFORMASI TEACHING FACTORY MELALUI INTEGRASI KEARIFAN LOKAL DI PENDIDIKAN VOKASI INDONESIA: DARI REPLIKASI INDUSTRI KE INKUBASI BUDAYA - Supriyadi, Supriyadi; Suryanto, Ahmad Eko; Yulando, Steven; Supatra, I Made (Steam Engineering, 2025)
Vocational education in Indonesia has extensively adopted the Teaching Factory (Tefa) model as a primary strategy to meet the demands of the industry. However, this model, which focused on the replication of modern industrial processes, faces challenges in producing graduates who are grounded in the context of local wisdom. This approach risks fostering a skills mismatch and potentially producing graduates who are uprooted from their cultural context. This article argues that the integration of local wisdom can fundamentally transform Tefa, shifting its paradigm from mere industrial replication to an incubator for local wisdom-based innovation. The goal is to achieve a vocational education system that is both economically relevant and deeply rooted in national identity. Employing a narrative literature review, this study synthesizes academic literature to address the urgency, form, opportunities, and challenges of this transformation. The findings indicate that transforming Tefa is crucial for fostering contextual learning, preserving cultural heritage, and unlocking new competitive advantages. This transformation manifests at the conceptual, curricular and pedagogical, product innovation, and community partnership levels. The analysis highlights that this process turns Tefa into a creative ecosystem, yet it must navigate the crucial tension between authenticity and commercialization. This article concludes that positioning local wisdom at the core of Tefa is a strategic move toward achieving a vocational education that is not only economically relevant but also firmly rooted in national identity.